Hypothyroidism and Leptin in Iraqi Patients with Chronic Kidney Disease (Baghdad Science Journal, 2021)
The present study aims at assessing the effects of chronic kidney disease (CKD) on thyroid hormone and leptin by evaluating the level of: leptin hormone along with thyroid hormone in CKD patients. The study has been conducted on 70 subjects, 50 patients with an age range between 20-50 years (25 males and 25 females) who were diagnosed to have CKD stage-5, and 20 normal controls whose ages ranged between 20-48 years (10 males and 10 females), who attended the Nephrology and Transplant Center in Medical City of Baghdad- Iraq from April 2018 to July 2018. The study showed a highly significant (P<0.01) increase in TSH level in CKD patients in comparison with controls. While T3 and T4 levels observed highly significant decrease (P<0.01) in CKD patients in comparison with their control groups; on the other hand, in Leptin levels, it has been demonstrated a highly significant (P<0.01) increase in CKD patients compared to the controls. Also there was a significant (P<0.05) positive correlation between TSH and Leptin, while the results showed a highly significant (P<0.01) negative correlation between T3, T4 and Leptin. To conclude, this study confirms that thyroid dysfunction and hyperleptinemia have been found to be very common in CKD patients and reveals the significant association between CKD progression and thyroid dysfunction and hyperleptinemia.